1993
DOI: 10.1577/1548-8659(1993)122<0074:iowcom>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Chemistry on Mercury Concentration in Largemouth Bass from Florida Lakes

Abstract: Harvestable‐size largemouth bass Micropterus salmoides were collected from 53 Florida lakes to determine relationships between mercury concentration in fish and physical and chemical lake characteristics. Diverse lakes with a broad range of sizes (15–181,000 hectares), pH (3.6–9.1), and alkalinities (1.2–128 mg/L as CaCO3) were sampled. Total mercury concentrations in axial muscle of individual fish ranged from 0.04 to 2.04 μg/g wet weight and were positively correlated with fish age (strongest correlation) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 36 publications
5
52
2
Order By: Relevance
“…Further assessment of Hg levels in Maryland sportfish is needed to protect human and wildlife health. Lange et al 1993 …”
Section: Discussionmentioning
confidence: 99%
“…Further assessment of Hg levels in Maryland sportfish is needed to protect human and wildlife health. Lange et al 1993 …”
Section: Discussionmentioning
confidence: 99%
“…Geographic differences in concentrations of p,pV-DDE, As, Hg, Se, and Zn were examined statistically using ANOVA, as were temporal differences by combining the results of our study with 1970-1986 NCBP data from Stations 16, 63, 64, and 65 (Schmitt et al, 1999b). Because concentrations of total Hg in predatory fish increase with size, age, or both (see for example Lange et al, 1993;Wiener et al, 2002), temporal and geographic differences in logtransformed length-adjusted (HgL) and weightadjusted (HgW) concentrations computed as described by Brumbaugh et al (2001) were also tested by ANOVA. A nominal a-level of 0.05 was used in all statistical tests unless otherwise indicated.…”
Section: Data Set Composition and Statistical Analysesmentioning
confidence: 99%
“…Biological factors such as age (Bache et al 1971;Grieb et al 1990;Lange et al 1993), size (MacCrimmon et al 1983: Grieb et al 1990: Lathrop et al 1991Fjeld and Rognerud 1993;Lange et al 1993) and diet (Phillips et al 1980;MacCrimmon et al 1983;Mathers andJohansen 1985: Cabana et al 1994) have been shown to influence mercury concentrations in fish, while surveys of fish mercury levels indicate that environmental variables such as Jake water pH (Wren and MacCrimmon 1983;Cope et al 1990;Grieb et al 1990: Wiener et al 1990: Wren et al 1991.Iake dystrophy (McMurtry et al 1989: Hâkanson et al 1990Sorensen et al 1990;Wren et al 1991), productivity (Hâkanson 1980;Lange et al 1993) and catchment area relative to lake area Lee and Iverfeldt 1991) are also important in influencing mercury accumulation in fish. Although much less is known about the factors affecting the accumulation of mercury in organisms at lower trophic levels in lakes, studies suggest that variables such as feeding habits and life cycle (Parkman and Meilli 1993), density (Sorensen et al 1990), lake water acidity (Meilli and Parkman 1988;Parkman and Meilli 1993).…”
Section: • •mentioning
confidence: 99%